Law Enforcement of the Crime of Child Intercourse through Marriage: A Review of Islamic Law and the SDGs (Decision No. 6/Pid.Sus/2022/PN. Mre) - Heru Pujo Handoko; Topo Santoso; Nashriana (Profetika: Jurnal Studi Islam, 2025)
Objective: This study aims to critically analyze the inconsistency between Indonesia’s national objectives, particularly the Sustainable Development Goals (SDGs), and the criminal law policies applied by the Public Prosecutor in cases involving sexual intercourse with minors resolved through marriage. Using Decision No. 6/Pid.Sus/2022/PN. Mre as a case study, the research seeks to formulate a model for legal reconstruction grounded in Islamic law and restorative justice that ensures optimal protection for child victims. Theoretical framework: The theoretical framework draws upon progressive legal theory, restorative justice theory, and child protection theory within the criminal justice system. These theories serve as a foundation for understanding the gaps between legal norms and their implementation, particularly in handling cases involving vulnerable victims like children. Literature review: The literature review explores the implementation of restorative justice in juvenile law, the prosecutorial role in minor-related offenses, and the policy discrepancies in protecting children's rights. Previous studies have often overlooked the intersection between cultural or religious practices and legal responses, especially in cases resolved through marriage rather than prosecution. Methods: Employing normative legal research methods, this study uses a legislative, conceptual, futuristic, and case approach to evaluate the legal basis and implications of resolving child sexual crimes through marriage. Results: The findings reveal that resolving such cases via marriage undermines the principles of child protection and justice. It neglects the child’s rights as emphasized in Islamic law and contradicts global commitments under the SDGs, particularly Goal 16 (Peace, Justice, and Strong Institutions). The study proposes a legal reconstruction model that reinforces collaboration between law enforcement and prosecutors to uphold restorative justice while ensuring legal certainty and the best interests of the child. Implications: This research contributes novel insights into reforming Indonesia’s criminal law policy concerning children, integrating Islamic legal principles with global human rights standards. Novelty: This study offers a legal reconstruction model of restorative justice child sexual intercourse cases, which balances legal certainty and the protection of children's rights in criminal justice proceedings.